2q36.3 is associated with prognosis for oestrogen receptor-negative breast cancer patients treated with chemotherapy - Li, Jingmei; Chang-Claude, Jenny; Rudolph, Anja; Hamann, Ute (Nature Communications, 2014)
Large population-based registry studies have shown that breast cancer prognosis is inherited. Here we analyse single-nucleotide polymorphisms (SNPs) of genes implicated in human immunology and inflammation as candidates for prognostic markers of breast cancer survival involving 1,804 oestrogen receptor (ER)-negative patients treated with chemotherapy (279 events) from 14 European studies in a prior large-scale genotyping experiment, which is part of the Collaborative Oncological Gene-environment Study (COGS) initiative. We carry out replication using Asian COGS samples (n=522, 53 events) and the Prospective Study of Outcomes in Sporadic versus Hereditary breast cancer (POSH) study (n=315, 108 events). Rs4458204_A near CCL20 (2q36.3) is found to be associated with breast cancer-specific death at a genome-wide significant level (n=2,641, 440 events, combined allelic hazard ratio (HR)=1.81 (1.49-2.19); P for trend=1.90 × 10−9). Such survival-associated variants can represent ideal targets for tailored therapeutics, and may also enhance our current prognostic prediction capabilities.
Authors: Jia N. Foo, Sajjad Rafiq, Marjanka K. Schmidt, Paul D.P. Pharoah, Kyriaki Michailidou, Joe Dennis, Manjeet K. Bolla,Qin Wang, Laura J. Van ‘t Veer, Sten Cornelissen, Emiel Rutgers, Melissa C. Southey, Carmel Apicella, Gillian S. Dite, John L. Hopper, Peter A. Fasching, Lothar Haeberle, Arif B. Ekici, Matthias W. Beckmann, Carl Blomqvist, Taru A. Muranen, Kristiina Aittomäki, Annika Lindblom, Sara Margolin, Arto Mannermaa, Veli-Matti Kosma, Jaana M. Hartikainen, Vesa Kataja, Georgia Chenevix-Trench, kConFab Investigators, Kelly-Anne Phillips, Sue-Anne McLachlan, Diether Lambrechts, Bernard Thienpont, Ann Smeets, Hans Wildiers, Jenny Chang-Claude, Dieter Flesch-Janys, Petra Seibold, Anja Rudolph, Graham G. Giles, Laura Baglietto, Gianluca Severi, Christopher A. Haiman, Brian E. Henderson,Fredrick Schumacher, Loic Le Marchand, Vessela Kristensen, Grethe I. Grenaker Alnæs, Anne-Lise Borresen-Dale, Silje Nord, Robert Winqvist, Katri Pylkäs, Arja Jukkola-Vuorinen, Mervi Grip, Irene L. Andrulis, Julia A. Knight, Gord Glendon, Sandrine Tchatchou, Peter Devilee, Robert Tollenaar,Caroline Seynaeve, Maartje Hooning, Mieke Kriege, Antoinette Hollestelle, Ans van den Ouweland, Yi Li, Ute Hamann, Diana Torres, Hans U. Ulmer, Thomas Rüdiger, Chen-Yang Shen, Chia-Ni Hsiung, Pei-Ei Wu, Shou-Tung Chen, Soo Hwang Teo, Nur Aishah Mohd Taib, Cheng Har Yip, Gwo Fuang Ho, Keitaro Matsuo, Hidemi Ito, Hiroji Iwata, Kazuo Tajima, Daehee Kang, Ji-Yeob Choi, Sue K. Park, Keun-Young Yoo, Tom Maishman, William J. Tapper, Alison Dunning, Mitul Shah, Robert Luben, Judith Brown, Chiea Chuen Khor, Diana M. Eccles, Heli Nevanlinna, Douglas Easton, Keith Humphreys, Jianjun Liu, Per Hall & Kamila Czene
Gesehen am 25.01.2021